“Estrategias didácticas lúdicas para niños de 5 años con ritmos de aprendizaje lentos” - Caiza Ortiz, Aida Estefanía (2022)
The present proposal aims to design activities that improve the slow learning process in children aged 4 to 5 years old who belong to initial education level, based on the research previously carried out as a project to obtain the degree of initial education teachers in the Technical University of Cotopaxi during the academic period October 2021-March 2022. The research method was qualitative since it was based on observation within the education establishment. The model on which the design of this guide focused is the constructivist model, what is sought is that the child will be specifically the creator of his own knowledge, thus giving the possibility of potentiating his development areas specially the cognitive one where the processes of attention, concentration and memory occur. The methodology used in the structure of the guide “The Magic of Learning” is the creative playful learning, didactic and methodological strategies providing activities centered on slow learning process, thus significantly benefiting the performance of children. For this, strictly qualified and adequate materials were investigated and created for each recreational activity that is going to be used by either a teacher or a parent. All the skills are correctly structured and consist of a name, description, objectives, materials or resources, development, time, age, graphics, video and evaluation sheet. It is important to emphasize that this proposal was made with a due analysis of education that merits the education of each infant that shows difficulties in the teaching-learning process.